An Overview of the Spindle Assembly Checkpoint Status in Oral Cancer. (3rd June 2014) - Teixeira, José Henrique; Silva, Patrícia Manuela; Reis, Rita Margarida; Moura, Inês Moranguinho; Marques, Sandra; Fonseca, Joana; Monteiro, Luís Silva; Bousbaa, Hassan
Abstract : Abnormal chromosome number, or aneuploidy, is a common feature of human solid tumors, including oral cancer. Deregulated spindle assembly checkpoint (SAC) is thought as one of the mechanisms that drive aneuploidy. In normal cells, SAC prevents anaphase onset until all chromosomes are correctly aligned at the metaphase plate thereby ensuring genomic stability. Significantly, the activity of this checkpoint is compromised in many cancers. While mutations are rather rare, many tumors show altered expression levels of SAC components. Genomic alterations such as aneuploidy indicate a high risk of oral cancer and cancer-related mortality, and the molecular basis of these alterations is largely unknown. Yet, our knowledge on the status of SAC components in oral cancer remains sparse. In this review, we address the state of our knowledge regarding the SAC defects and the underlying molecular mechanisms in oral cancer, and discuss their therapeutic relevance, focusing our analysis on the core components of SAC and its target Cdc20.